2015
DOI: 10.1038/srep14993
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide alters the differentiation of mouse embryonic stem cell into cardiomyocytes

Abstract: Chronic arsenic exposure is associated with increased morbidity and mortality for cardiovascular diseases. Arsenic increases myocardial infarction mortality in young adulthood, suggesting that exposure during foetal life correlates with cardiac alterations emerging later. Here, we investigated the mechanisms of arsenic trioxide (ATO) cardiomyocytes disruption during their differentiation from mouse embryonic stem cells. Throughout 15 days of differentiation in the presence of ATO (0.1, 0.5, 1.0 μM) we analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 61 publications
3
26
1
Order By: Relevance
“…In newborn and pregnant mice, structural changes in the thymus gland were investigated [ 14 ]. Several in vitro studies on female reproduction revealed that long term exposure of arsenic is associated with reduced lactation, abortion, low birth weight [ 15 ] and toxicity of embryonic cells [ 16 ]. Undeniably arsenic in drinking water that exceeds the admissible limit leads to disturbances in reproduction [ 17 ], undesirable pregnancy outcomes [ 18 ], and spontaneous abortion [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In newborn and pregnant mice, structural changes in the thymus gland were investigated [ 14 ]. Several in vitro studies on female reproduction revealed that long term exposure of arsenic is associated with reduced lactation, abortion, low birth weight [ 15 ] and toxicity of embryonic cells [ 16 ]. Undeniably arsenic in drinking water that exceeds the admissible limit leads to disturbances in reproduction [ 17 ], undesirable pregnancy outcomes [ 18 ], and spontaneous abortion [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the human prostate, PrSPCs give rise to basal cells, luminal PrECs, and rare neuroendocrine cells (Strand and Goldstein 2015). Because iAs alters differentiation in a variety of stemprogenitor cells (Bain et al 2016;McCoy et al 2015;Rebuzzini et al 2015;Yen et al 2010), we tested whether iAs influences this process in PrSPCs. Primary PrSPCs cultured for 7 d from diseasefree PrECs were isolated and mixed with embryonic rat urogenital sinus mesenchyme (UGM) and grafted under renal capsules of nude mice.…”
Section: Self-renewal and Differentiation Of Prspcs Treated With Or Wmentioning
confidence: 99%
“…Together, these results confirm the teratogenicity of iAs as reported previously based on animal studies (Hood et al ., ; Leonard & Lauwerys, ; Chaineau et al ., ; Machado et al ., ). In contrast, recent reports claimed ESC differentiation into cardiomyocytes, skeletal muscles and neurons was impaired or inhibited by iAs exposure (Liu & Bain, ; Rebuzzini et al ., ; Wang et al ., ). However, we did not investigate the directed differentiation of ESCs into specific cell lineages in the presence of iAs.…”
Section: Discussionmentioning
confidence: 99%